Análisis de redes sociales de las redes de colaboración en I+D+i en el Perú (2007-2018) - Bazán Borja, Mario Francisco (2022)
Between 2007 and 2018, Peru increased its capacities to promote science, technology, and innovation through the implementation of competitive financing mechanisms that, due to their design, have contributed to the formation of collaborative networks for scientific research, technological development, and innovation. These collaborative networks for innovation are central to the adoption, generation, adaptation, transmission and valorization of knowledge, technologies, and innovations. This work employs social network analysis to identify the characteristics of collaborative networks at the national, regional, and interregional levels, as well as to measure the role of actor networks, both at the national, regional, and interregional levels, with respect to the diffusion of knowledge and the generation of collaborative networks created from competitive funding mechanisms. The thesis proposes a characterization of the regional innovation systems considering the composition of the collaboration networks generated by the funded projects; identifies the regions that would be forming inter-regional innovation systems; and shows the inter-temporal value of longterm collaborations between actors at the national level. The main conclusions include the leading role played by academic organizations in the national innovation system, the different degrees of maturity of regional innovation systems and a classification for Peru, and a proposal for interregional integration based on scientific and technological knowledge in the country.